Evaluating the Impact of Radiation Safety Training on Staff Nurse Knowledge: Pre and Post Assessment - Sivaprakash Vijayarajan*, Anita Soundarapandian, Kreethi Suresh kumar (Journal of Neonatal Surgery, 2025)
Background: Radiation safety is critical in healthcare, particularly for staff nurses frequently exposed to various imaging modalities. Ensuring their knowledge of radiation protection is vital for both patient care and their safety. Aims: This study aims to evaluate the effectiveness of a targeted radiation safety training program by comparing the knowledge of staff nurses before and after the training. Settings and Design: Conducted at Panimalar Medical College Hospital & Research Institute, this pre- and post-assessment study involved 141 staff nurses and 10 operation theatre technicians. Methods and Material: The training covered essential topics, including proper use of TLD badges, AERB guidelines, and the ALARA principle. A standardized questionnaire was administered before and after the training to assess knowledge improvement. Statistical Analysis Used: A paired t-test was employed to compare pre- and post-training scores, and descriptive statistics were used to analyse the results. Results: The mean score significantly increased from 2.90 pre-training to 9.15 post-training, indicating a substantial improvement in knowledge. The training effectively enhanced the nurses' understanding of radiation safety, with statistically significant results (p < 0.0001). Conclusion: The radiation safety training program was highly effective in improving the knowledge of staff nurses, leading to better preparedness in handling radiological procedures safely. This improvement underscores the importance of regular, targeted training to ensure a safer healthcare environment.